2008
DOI: 10.1182/blood-2007-11-120998
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-specific Th17-polarized cells eradicate large established melanoma

Abstract: IntroductionThe role of CD4 ϩ cells in antitumor immunity remains controversial and poorly understood. 1,2 They are known to mediate potent therapeutic effect in the setting of hematopoietic stem cell allotransplantation and donor lymphocyte infusion in hematologic malignancy, 3,4 but antigen-specific T helper (Th) cells have been studied to much lesser extent. A lack of clarity regarding CD4 ϩ cells is due, in no small part, to the complexity of their biology. CD4 ϩ T cells can differentiate into diverse subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

32
721
5
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 722 publications
(773 citation statements)
references
References 91 publications
32
721
5
3
Order By: Relevance
“…In fact, our data are consistent with recent findings showing that Th17 cells producing IFN-g are capable of mediating regression of established tumors in some murine models. 44,46,47 Collectively, our data suggest that, in our model, Th17-polarized cells mainly mediated tumor 45 Further studies with a selective depletion of effector cells will help to elucidate the exact role that these cells have in the observed antitumoral effect. In summary, we have shown that hybrids of tumor cells and DCs transduced with CD40L induce systemic antitumor immunity, which, in contrast to untransduced fused cells, can eradicate established tumors.…”
Section: Fusion Cell Vaccine With Cd40l Gene Modification E Alvarez Ementioning
confidence: 59%
See 1 more Smart Citation
“…In fact, our data are consistent with recent findings showing that Th17 cells producing IFN-g are capable of mediating regression of established tumors in some murine models. 44,46,47 Collectively, our data suggest that, in our model, Th17-polarized cells mainly mediated tumor 45 Further studies with a selective depletion of effector cells will help to elucidate the exact role that these cells have in the observed antitumoral effect. In summary, we have shown that hybrids of tumor cells and DCs transduced with CD40L induce systemic antitumor immunity, which, in contrast to untransduced fused cells, can eradicate established tumors.…”
Section: Fusion Cell Vaccine With Cd40l Gene Modification E Alvarez Ementioning
confidence: 59%
“…42,43 The fact that both IL-2 and IFN-g secretions have been detected mainly in cells from FC-CD40L-vaccinated mice suggests that Th1 cells could be involved in an antitumoral effect. However, as both human and murine Th17 cells produce IL-2 and IFN-g (that is, the so-called Th17-1), 44,45 we cannot rule out Th17 cells as the main source of this cytokine. In fact, our data are consistent with recent findings showing that Th17 cells producing IFN-g are capable of mediating regression of established tumors in some murine models.…”
Section: Fusion Cell Vaccine With Cd40l Gene Modification E Alvarez Ementioning
confidence: 99%
“…To our knowledge, this is the first report demonstrating tumor-promoting properties of gd T cells, which is quite different from the generally reported tumor-inhibiting properties of skin-resident Vg5 1 gd T cells. Recent studies have shown that tumor antigen-specific Th17 or Tc17 cells, which were induced in vitro, were converted into IFN-g-producing cells after transfer into tumor-bearing mice and subsequently eradicated tumor cells [45,46]. In contrast, IL-17-producing gd T cells did not produce IFN-g in the tumor microenvironment in parallel with the decrease of their cytotoxic function.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we now investigated whether Th1 cell therapy or introduction of Th1 immunity by IL-12 can induce a plasticity in IL-17-producing gd T cells, namely, alter pro-to anti-tumor IL-17-producing gd T cells. Recently, it has been reported that IL-17-producing cells exhibited anti-tumor immunity in vivo in an IFN-g-dependent manner [46]. Therefore it might be possible to control pro-tumor and anti-tumor properties of IL-17-producing gd T cells by introducing Th1-dominant immunity at tumor-local site.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known, however, about the risk of autoimmune pathology caused by CD4 1 effector T cells and the mechanisms regulating their functions against cancerous and normal tissues. Some insight can be gained from a recent publication that found the anti-tumor potency of CD4 1 T cells was directly related to their capacity to produce depigmentation in the skin [13], reinforcing the concept that these two processes are linked.…”
Section: Introductionmentioning
confidence: 88%